Promoting collaborative skills in online university: comparing effects of games, mixed reality, social media, and other tools for ICT-supported pedagogical practices - Martínez-Cerdá, Juan Francisco; Torrent-Sellens, Joan; González-González, Ines (Behaviour and Information Technology, 2019)
This article analyses the development of collaborative skills through nine tools for information and communication technologies (ICT)-supported pedagogical practices, which are used in online universities. Using survey data for 930 online students at the Open University of Catalonia and partial least squares path modelling estimation techniques, three main findings emerged from the study. First, collaborative skills are directly explained by gamification and the use of mixed reality and social media in a socio-technical online learning context. Second, other tools for ICT-supported pedagogical practices (media content, wikis, open educational resources, personal webpages, personal cloud, and sharing files with fellow students and lecturers on the cloud) are not significant on collaborative skills development, when compared to use of games, mixed reality, and social media. Third, the analysis of indirect effects suggests that all four socio-technical factors (ICT, learning tasks, students, and organisation) existing in online university play a decisive, positive and significant role in collaborative skills development. Finally, these results are shown in science, technology, engineering, and mathematics (STEM) and non-STEM studies. Thus, gamification, mixed reality, and sharing files are significant ICT-supported pedagogical practices in STEM studies. On the other hand, gamification is the only significant tool in non-STEM studies. Results are very useful for new approaches to design a framework for learning-team effectiveness in computer-supported collaborative learning.
Keywords: collaborative skills; e-learning; gamification; ICT-supported pedagogical practices; partial least square–structural equation modelling; STEM; Scopus; JCR